Influence of carrageenan and total solids content on the rheological properties of lactic beverage made with yogurt and whey - Penna, A. L B [UNESP]; Oliveira, M. N.; Tamime, A. Y. (Wiley, 2003)
The purpose of this work was to study the influence of carrageenan level (X 1) and total solids content of yogurt/whey mixture (X 2) on starter culture fermentation time, physicochetnical properties (pH, fat and total solids contents) and rheological characteristics of lactic beverages using response surface methodology. The physicochemical characteristics of the lactic beverages were similar to those of commercial products. All beverages showed non-Newtonian fluid behavior with thixotropy and yield stress. The total solids content of the lactic beverages had a greater influence on the rheological behavior of these products than the carrageenan level. Wide ranges of consistency measurements were observed by varying the stabilizer level and total solids content.
Keywords: Lactic beverages; Fermentation; Mixtures; pH effects; Rheology; Yield stress; Dairy products